2018
DOI: 10.1177/0031512518809734
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Psychological and Physiological Effects of Varying the Volume of High-Intensity Interval Training in Healthy Men

Abstract: We assessed the short-term effects of varying the volume of high-intensity interval training (HIIT) on psychological and physiological responses of 23 healthy adult males ( M = 21 years; M peak oxygen uptake [VO2peak] = 47.2 ml·kg−1·min−1). Participants were randomly assigned to low- and very-low-volume HIIT groups and engaged in nine supervised exercise sessions over three weeks. The low-volume HIIT group performed 8-12 60-second work bouts on a cycle ergometer at the peak power output achieved during the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…Although our hypothesis of a favoring the long trial HIIE was rejected, our protocol was designed with support from a study that evaluated the peak-end rule in other context such as an aversion experience (Kahneman et al, 1993). Specifically, we followed Kahneman et al (1993) design and kept the same intensity over the short-trial because the effort accumulated over time induces an increase in RPE and a decrease in affect (Da Silva Machado et al, 2019;Frazão et al, 2016;Kellogg et al, 2019;Marques et al, 2020;Olney et al, 2018); thus, generating the worst values of psychological responses at the end of the trial (peak of intensity). Indeed, we added 50% duration with a gradual decrease in intensity in the long-trial, and although we did not find statistical differences for the global scales, 63.3% of participants found the shortest protocol the most intense protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our hypothesis of a favoring the long trial HIIE was rejected, our protocol was designed with support from a study that evaluated the peak-end rule in other context such as an aversion experience (Kahneman et al, 1993). Specifically, we followed Kahneman et al (1993) design and kept the same intensity over the short-trial because the effort accumulated over time induces an increase in RPE and a decrease in affect (Da Silva Machado et al, 2019;Frazão et al, 2016;Kellogg et al, 2019;Marques et al, 2020;Olney et al, 2018); thus, generating the worst values of psychological responses at the end of the trial (peak of intensity). Indeed, we added 50% duration with a gradual decrease in intensity in the long-trial, and although we did not find statistical differences for the global scales, 63.3% of participants found the shortest protocol the most intense protocol.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in which researchers manipulated different HIIE variables (Martinez et al, 2015;Townsend et al, 2017;Da Silva Machado et al, 2019;Kellogg et al, 2019). Some reported higher enjoyment and affect with shorter duration intervals (Martinez et al, 2015;Townsend et al, 2017), others found that low-volume HIIE led to higher enjoyment and affect (Da Silva Machado et al, 2019), and one showed that imposed intensity induced higher affect than self-selected HIIE intensity (Kellogg et al, 2019). After further research has enhanced our understanding of affect and RPE during HIIE protocols (i.e., the experiencing self), a second future advance would be to evaluate how memories of the peak and end sessions are formed (i.e., the remembering self).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 , 46 , 47 Two studies in untrained adults have examined changes in RPE with HIIT and both have found reductions. 29 , 48 In the present study RPE responses to HIIT were modulated by bout duration. Our findings of a reduction in perceptual and affective responses to HIIT10 only suggest that these may be mostly driven by metabolic, rather than cardiovascular, adaptations.…”
Section: Discussionmentioning
confidence: 51%
“…Por otro lado, en una prueba incremental MART (Maximal Anaerobic Running Test) se identificó que en los períodos de esfuerzo (20 seg) existe un mayor aporte energético anaeróbico (62,6 % aláctico y 10,9 % láctico) que el aeróbico (26,5 %), mientras que, al evaluar la prueba total, el componente aeróbico (65,4 %) fue más alto que el anaeróbico (29,5 % aláctico y 5,1 % láctico) (16). Al comparar un protocolo interválico corto (8x20 seg) y largo (4x4 min) se evidenció una velocidad de carrera más alta significativamente en el trabajo corto (17), esto se debe a que el entrenamiento HIIT de muy bajo volumen es percibido como menos extenuante y más placentero con respecto al de bajo volumen, además que permite mejorar la capacidad anaeróbica (18).…”
Section: Esfuerzos Intermitentes Cortos De Intensidades Maximalesunclassified